Mempertimbangkan Kembali Orientasi Gerakan Bantuan Hukum Indonesia - Wiratraman, Herlambang P (Faculty of Law, Parahyangan Catholic University, 2016)
AbstractThis article discusses the practice of individual and structural legal aid and how it has been contextualized within the dynamic of Indonesian politics and law making (especially related to Law No. 16 of 2011 re. Legal Aid). The main question addressed is the extent to which legal aid succeed in pushing real legal reform and contribute to the effort of realizing a just society. Unfortunately, the author discovers that legal reform initiated post Soeharto, initially held to be positive, failed to fulfills its intended goals. Instead law implementation and enforcement remains vulnerable to external pressure and in fact had been unable to stop on-going human rights violations and widespread corruption.